Political Economy of Vulnerability a Gendered Analysis of Drought and Livelihood Struggles Among Farming Communities in Puruliya (West Bengal, India) (Glocalism: Journal of Culture, Politics and Innovation, 2019)
Globalisation is a complex phenomenon that humankind is facing in the pre- sent times. However, one cannot deny that there is less agreement as to which aspects are “good” or “bad” and for whom. Despite understanding globalisation as offering many opportunities, it has placed pressures on the global environment, straining the carrying capacity of vulnerable ecosystems and the people dependent on them. Specifically, marginalized women whose access to resources are limited, are often doubly exposed to forces of globalisation and climate variations. The aim of this paper is therefore to examine the contemporary global and local forces shaping vulnerability among women to drought. The paper is based on qualitative research carried on in a traditional farming community in a village in eastern India. The findings of this paper show that globalisation in-itself functions as a dynamic macro pressure on the root causes like patriarchy and access to resources, in addition to deforestation, land fragmentation, migration and commercialisation of agriculture. The women have been severely im- pacted through forces of globalisation: technological modernisation as well as market reforms. In this context there has been changes in women’s work role and gender relations leading to feminisation of labour, single women headed households, food insecurity and unsafe habitats, thus, impacting women’s day to day existence. Globalisation acting as a key macro force, however has failed to address the micro level issues like enhancing women’s skills towards livelihood diversification, education and learning opportunities; strengthening local markets and access to key resources to overcome discrimination, achieve equality and improved state of well-being.
Keywords: women; globalisation; drought; vulnerability; farming